2021
DOI: 10.1002/ejp.1876
|View full text |Cite
|
Sign up to set email alerts
|

Insight into pain syndromes in acute phase of mild‐to‐moderate COVID‐19: Frequency, clinical characteristics, and associated factors

Abstract: Background Pain has been frequently described as a clinical feature of COVID‐19, and the main pain syndromes that have been associated with the acute phase of this disease so far are headache, myalgia, arthralgia, and neuropathic pain. Understanding the characteristics of pain symptoms is crucial for a better clinical approach. Methods Patients who were diagnosed as having COVID‐19 using reverse transcription‐polymerase chain reaction were included in the study. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 57 publications
3
35
0
Order By: Relevance
“…The prevalence of neuropathic pain in our sample of COVID-19 survivors (25%) was similar to the rate provided by Oguz-Akarsu et al [ 9 ] by using a telephone interview but self-reported. Current prevalence data of neuropathic symptoms in COVID-19 survivors (25%) is higher than the prevalence of neuropathic symptoms reported by a nationwide study (6.9%) in people with chronic pain [ 19 ], supporting the expected increase in the prevalence of neuropathic pain due to COVID-19 [ 5 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The prevalence of neuropathic pain in our sample of COVID-19 survivors (25%) was similar to the rate provided by Oguz-Akarsu et al [ 9 ] by using a telephone interview but self-reported. Current prevalence data of neuropathic symptoms in COVID-19 survivors (25%) is higher than the prevalence of neuropathic symptoms reported by a nationwide study (6.9%) in people with chronic pain [ 19 ], supporting the expected increase in the prevalence of neuropathic pain due to COVID-19 [ 5 ].…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, McWilliam et al [ 8 ] reported neuropathic pain as a post-COVID sequelae. A cohort study recently reported that almost 25% of patients with post-COVID pain exhibit neuropathic symptoms; however, this study collected self-reported symptoms throughout a telephonic interview [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of the European Journal of Pain you will find the article by Oguz‐Akarsu and collaborators entitled “Insight into Pain Syndromes in Acute Phase of Mild‐to‐Moderate COVID‐19: Frequency, Clinical Characteristics, and Associated Factors” (Oguz‐Akarsu et al, 2021 ). This observational cohort was one of the handful yet to have described in detail the phenomenon of pain during acute COVID‐19 and, to the best of our knowledge, the first to have examined the associations between distinct pain syndromes in such context.…”
Section: What Lies Behind and Beyond Acute Covid‐19 Pain?mentioning
confidence: 99%
“…An increasing number of studies reported the presence of musculoskeletal post-COVID pain in up to 60% of the COVID-19 survivors [ 6 , 7 , 8 , 9 ]. The number of studies investigating the prevalence of neuropathic post-COVID pain is lower in relation to those assessing musculoskeletal post-COVID pain [ 10 , 11 ]. These studies have observed that 20% of individuals with post-COVID pain also exhibit neuropathic pain features [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%